A Weaning Protocol for Venovenous Extracorporeal Membrane Oxygenation With a Review of the Literature. Issue 6 (18th January 2018) - Grant, April A.; Hart, Valerie J.; Lineen, Edward B.; Badiye, Amit; Byers, Patricia M.; Patel, Amit; Vianna, Rodrigo; Koerner, Michael M.; El Banayosy, Aly; Loebe, Matthias; Ghodsizad, Ali
Abstract: Several articles have discussed the weaning process for venoarterial extracorporeal membrane oxygenation; however, there is no published report to outline a standardized approach for weaning a patient from venovenous extracorporeal membrane oxygenation (ECMO). This complex process requires an organized approach and a thorough understanding of ventilator management and ECMO physiology. The purpose of this article is to describe the venovenous ECMO weaning protocol used at our institution as well as provide a review of the literature.